Upravljanje prostoživečih živali čezmejnega območja Julijskih Alp na primeru alpskega kozoroga in severnega (alpskega) gamsa - Neve Repe, Andreja (Gozdarski vestnik, 2023)
Ecological connectivity enables natural processes such as gene flow, migration, and species range shifts, and is therefore important for the long-term conservation of species and their habitats. To ensure ecological connectivity, the physical connection of habitat patches, and unimpeded movement of the organisms between them are essential. Barriers for transboundary movement of organisms between countries are the differences in the politics, legislation, and management of wildlife. Inconsistent management of wildlife can cause problems in the connectivity of some species’ populations on both sides of the country border, which affects the movement and behaviour of the animals. Therefore, trans-boundary protected areas play an important role in ensuring ecological connectivity between two or more countries. Two important wildlife species for the Alpine area are Alpine ibex (Capra ibex) and northern (Alpine) chamois (Rupicapra rupicapra). Therefore, in the AlpBioNet2030 and DINALPCONNECT projects, we analysed the condition and management of both species in the Julian Alps trans-boundary area (size 289.660 ha), situated between Italy and Slovenia. Furthermore, we proposed changes in management to improve the populations’ condition and ensure ecological connectivity of the habitat for the species in the wider trans-boundary area. Since 2017, we have carried out four trans-boundary workshops with stakeholders from Italy and Slovenia (representatives of hunters, landowners, protected area managers, foresters, decision-makers on the national and regional level (ministries, municipalities), and nature conservationists). The result of the participative process is a trans-boundary management concept of the Alpine ibex and northern (Alpine) chamois populations and their habitat, which incorporates the vision and strategy of the trans-boundary management and action plan in the Julian Alps trans-boundary area.
Keywords: Alpine ibex; alpski kozorog; čezmejno upravljanje; ecological connectivity; ekološka povezljivost; Julian Alps; Julijske Alpe; northern (Alpine) chamois; severni (alpski) gams; trans-boundary management